2010
DOI: 10.1007/s11252-010-0137-4
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of growth medium and leachate from green roof systems in south-central Texas

Abstract: Installation of intensive and extensive green roofs is becoming popular for reducing runoff from impervious surfaces in many cities around the world. Most studies on runoff quality from green roofs have been conducted in cooler northern climates. We examined the losses and gains of nutrients, cations and selected anions in planted and unplanted growth medium and compared these to initial growth medium (IGM) typically used for green roof modules in south-central Texas. Water extracts of growth medium and leacha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 33 publications
5
42
2
Order By: Relevance
“…Similar results were obtained for organic matter (Figure 8), phosphorus, and coliforms, with concentrations for GRs that were significantly higher than the control cases' concentrations (Table 3). These are similar to results presented in previous studies, indicating GRs as a source of organic matter [7,46], phosphorus [22,24,25,47,48], pathogens [48], and total dissolved solids [1,30], as well as the pH neutralization effect from GRs [1,22,25,26,31,[49][50][51][52]. GRs had significantly higher concentrations for total Kjeldahl nitrogen (TKN), nitrates, and nitrites than the control cases, confirming the findings of Aitkenhead-Peterson et al [46], Greogoire and Clausen [53], Moran et al [54], and Whittinghill et al [55].…”
Section: Water Quality Resultssupporting
confidence: 91%
“…Similar results were obtained for organic matter (Figure 8), phosphorus, and coliforms, with concentrations for GRs that were significantly higher than the control cases' concentrations (Table 3). These are similar to results presented in previous studies, indicating GRs as a source of organic matter [7,46], phosphorus [22,24,25,47,48], pathogens [48], and total dissolved solids [1,30], as well as the pH neutralization effect from GRs [1,22,25,26,31,[49][50][51][52]. GRs had significantly higher concentrations for total Kjeldahl nitrogen (TKN), nitrates, and nitrites than the control cases, confirming the findings of Aitkenhead-Peterson et al [46], Greogoire and Clausen [53], Moran et al [54], and Whittinghill et al [55].…”
Section: Water Quality Resultssupporting
confidence: 91%
“…This increase in organic matter agrees with the Köhler and Poll (2010) study discussed above and with the findings of Getter et al (2007) who reported that organic matter nearly doubled from 2.33 to 4.25 % in just 5 years where the primary component of the substrate was heatexpanded slate. Similarly, Getter et al (2009b) reported that the amount of carbon sequestered on shallow sedum based roofs increased with age and that 100 g C/ cm 2 (57.8 oz/in 3 ) were sequestered during the first 2 years after installation of 6 cm (2.4 in) deep plots.…”
Section: Old Green Roofs In Germanysupporting
confidence: 92%
“…Zhang et al (2007) indicate that green roof "soil erosion" induced by winds decreases with higher levels of plant cover. Roots bind plant masses to the substrate, thus providing a windbreak from erosive forces.…”
Section: Stability Of Substrate and The Entire Green Roof Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Aitkenhead-Peterson et al mentioned that phosphorus can be released from the soil layer in a green roof. However, the concentrations of NH4+ and NO3− decrease when a green roof system is adopted [13]. Figure 9.…”
Section: Purification Using a Membrane Techniquementioning
confidence: 99%